Nursing Challenges in Pediatric Cancer Care: Scoping Review - Naviati, Elsa; Allenidekania, Allenidekania; Afiyanti, Yati (Media Keperawatan Indonesia, 2024)
The successful treatment of children with cancer is a long cycle that requires cooperation between health workers, families and children. Various problems can arise as a result of the illness and treatment the child receives. The aim of this study was to identify the challenges faced by nurses in caring for children with cancer. The research method used was a scoping review because the researcher wanted to cover all the challenges faced by nurses in all aspects of care and treatment in cancer children. Results: challenges come not only from the nurse but also the child and their parents. Challenges from nurses: cancer knowledge and resource development and the various issues that arise in families and children with cancer. Challenges from the child, parents and family: accessing health services and getting support due to life changes after the child is diagnosed with cancer. Conclusion: challenges come from many aspects and good collaboration is needed to turn challenges into successes in the care and treatment of children with cancer.